PENERAPAN MODEL GREEN SUPPLY CHAIN MANAGEMENT UNTUK PENGEMBANGAN INDUSTRI BATIK TULIS MADURA DENGAN GSCOR DAN ANP - Ismiyati; Darmawan, Aang Kisnu; Bakir (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
Research on the implementation of Green Supply Chain Management (GSCM) in every business unit is very important considering the urgent environmental issues. This research focuses on the assessment of the GSCM process and performance measurement to determine the performance value of GSCM in the Madura Batik Writing Industry. The methods used are the greenSCOR method and the analytical network process (ANP) method. The Green SCOR method is used to identify and measure environmental and sustainability performance in the supply chain including The 5 core processes are planning, procurement, production, delivery and return. Meanwhile, the ANP method is used to determine the weight of importance of each core process. The results of the research on measuring the performance of the supply chain of the written batik industry using the GreenSCOR model showed a value of 65.5225, showing that the written batik industry in Pamekasan Regency is included in the category of "Avarange" related to the measurement of supply chain management performance reflecting the overall performance companies in the batik tulis industry. The weighting results of the Analytic Network Process (ANP) method show that the criteria "Make" (0.34) and "Plan" (0.31) are the most important in performance assessment, followed by "Source" and "Deliver" with weights of 0.16, and 0.10 respectively while "Return" has the lowest weight (0.06). The implication of this research is the importance of strengthening planning and efficiency in the production process. This research can produce valuable publications in academic journals related to supply chain management, sustainability, and creative industries. The results of these studies can serve as a reference for practitioners, researchers, and policymakers in their efforts to implement sustainable practices in the batik writing industry and other industries.